EU-Supported Regional Development After 2007: Lessons Learnt and Future Priorities of the Greek Regions Falling Under the New "Competitiveness" Objective Programmes - Manolis Christofakis; Nicholas Karachalis; Athanassios Papadaskalopoulos (European Regional Science Association (ERSA), 2006)
Next year (2007) is expected to be a milestone for the regional policy of Greece. For the first time since the EU launched the programmes which are co-funded by the Structural Funds, Greek regions are excluded from the Objective 1 "Convergence" programmes of the 2007-2013 programming period. Two regions, Sterea Ellada and Southern Aegean have been included in the phasing - in group of NUTS II regions which are falling under the new "Regional Competitiveness and Employment" objective since they have exceeded the 75% boundary of the GDP per capita of the EU both in relation with the older 15 and the 25 current member states. Hence, apart from the reduction funding compared to the current period, they are obliged to redefine their developmental priorities and to adjust the programming context according to the new circumstances in line with the Lisbon and Gothenburg objectives. Within this context the preparation calls for the adjustment to the new circumstances and the exploration of the most efficient way to continue and empower the developmental path. In addition to these, some important matters such as the actual developmental position of these regions, the sectors where cohesion hasn't been achieved, the new challenges and the experience that has been gained and to what extent it is being used as a learning process have to be explored The article aims to contribute to the ongoing conversation regarding the ways by which Sterea Ellada and Southern Aegean regions can utilize the Structural Funds in the new programming period, based on their experience until today, but also on the possibilities which they are being offered as "phasing – in" regions of the "Competitiveness and Employment" objective according to the new context of regional policy. To these directions, the general outlines of the future perspectives of the regional priorities of the European Union will be presented initially, both for the current and the next programming period. A comparative description of the socio-economic position of the two regions within the European Union is given next, followed by a discussion of the current programming experience and some implementation issues and lessons learnt. Finally, suggestions and some policy priorities as well as the conclusions of the analysis will be presented.
Keywords: 330